Isometric and swallowing tongue strength in healthy adults123. (5th August 2013) - Todd, J. Tee; Lintzenich, Catherine Rees; Butler, Susan G.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The tongue contributes to a safe swallow. It facilitates bolus control during mastication, maintains a bolus in the oral cavity to prevent premature entry of the bolus into the hypopharynx, and helps generate pressure in the hypopharynx during swallowing. This study examined isometric tongue strength and tongue pressure measured during swallowing in healthy young and older adults. Study Design Prospective group design. Methods One hundred twenty‐six healthy individuals who were recruited as part of a larger study on swallowing participated in this study. Participants were divided into three age groups: 20 to 40 years, 41 to 60 years, and ≥61 years. A KayPentax Digital Swallowing Workstation with an air‐filled bulb array was placed on the tongue of each participant (anterior to posterior). Participants completed three isometric tongue presses and three swallows. Results Repeated measures analyses of variance revealed a significant main effect of age (P = .01) and gender by tongue bulb location interaction (P = .02) for isometric tongue strength. That is, older adults had lower isometric tongue strength than young adults, and females had a greater difference between anterior and posterior tongue strength than males. Tongue strength during swallowing yielded significantly greater anterior versus posterior tongue pressure. Conclusions This study comprises one of the largest in terms of number of healthy participants reported to date and confirms previous findings that isometric tongue strength decreases with age. Furthermore, given young and older adults generate similar swallowing pressures, swallowing is a submaximal strength activity, yet older adults have less functional reserve. Laryngoscope, 123:2469–2473, 2013